1999
DOI: 10.1046/j.1365-2206.1999.00087.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and treatment outcomes in children’s homes

Abstract: A follow‐up study of 141 young people in 48 children’s homes examined changes in their moods, relationships with their family and adjustment. The average scores of the group on these variables changed little between first interview and follow‐up 6–9 months later. However, some individuals improved and others deteriorated. Improvements in family relationships were more likely in homes where the head of home could describe strategies for fostering family ties. Improvements in adjustment were also more likely in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1
5

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 5 publications
0
14
1
5
Order By: Relevance
“…LAC quoted in the literature (Gibbs and Sinclair, 2000;Morgan, 2008) identify the same benefits from positive relationships as did the young adults from The Orchards but they also make it clear that the gains are more extensive than our interviewees indicate. These gains are in the short- (Happer, McCreadie and Aldgate, 2006;Rainer, 2008), medium- (Gibbs and Sinclair, 1999;Ward, Kansinski, Pooley and Worthington, 2003) and long-term (Martin and Jackson, 2002). Receiving 'support' and 'encouragement', for example, are mentioned especially frequently among more immediate benefits (Happer et al, 2006;HM Government, 2006).…”
Section: Relationshipsmentioning
confidence: 99%
“…LAC quoted in the literature (Gibbs and Sinclair, 2000;Morgan, 2008) identify the same benefits from positive relationships as did the young adults from The Orchards but they also make it clear that the gains are more extensive than our interviewees indicate. These gains are in the short- (Happer, McCreadie and Aldgate, 2006;Rainer, 2008), medium- (Gibbs and Sinclair, 1999;Ward, Kansinski, Pooley and Worthington, 2003) and long-term (Martin and Jackson, 2002). Receiving 'support' and 'encouragement', for example, are mentioned especially frequently among more immediate benefits (Happer et al, 2006;HM Government, 2006).…”
Section: Relationshipsmentioning
confidence: 99%
“…In this connection, residential care homes are increasingly seen as potential sites for the provision of mental health services and it has been suggested that residential care staff could extend their roles to include work with a more overt, therapeutic slant (Gibbs & Sinclair, 1999;Nunno et al, 2003). In order to develop this potential, The Department of Health, Social Services and Public Safety Northern Ireland (DHSSPS) has recently provided funding to establish therapeutic approaches in residential children's homes across Northern Ireland (Macdonald et al, 2012).…”
Section: Treatment Gapmentioning
confidence: 99%
“…Similarly, consumers in the control group assigned to different "regular" AFDC caseworkers represented distinct clusters. In another study, Gibbs and Sinclair (1999) examined treatment outcomes of 141 youths living in 48 children's homes. Predictors of child-level outcomes included child characteristics, but also home-level characteristics, such as emphasis on building a child-family relationship.…”
Section: Outcome Studiesmentioning
confidence: 99%